PENGARUH KEDALAMAN MUKA AIR TANAH TERHADAP GENANGAN DI WILAYAH KECAMATAN PASAR MINGGU, PROVINSI DKI JAKARTA: THE EFFECT OF GROUNDWATER DEPTH ON FLOODING IN THE REGION OF PASAR MINGGU DISTRICT, DKI JAKARTA PROVINCE - Farhan Ryandi Nugraha; Abdurrachman Assegaf; Suherman Dwi Nuryana (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
The flood disaster that hit the capital city cannot be separated from the lives of the people living around it. Every time it rains, the city of Jakarta has never been separated from notifications about inundation or flooding events. The purpose of this study is to review the factors that cause inundation or flooding in the city of Jakarta and its surroundings, especially the Pasar Minggu sub-district, on the influence of the depth of the groundwater table. The author collects library materials in the form of lithological conditions of the research area, annual rainfall data in the research area and performs direct measurements of the depth of the groundwater table in the research area. The results of this study are to provide a review regarding the research area is a flooded area so that after all this inundation event is difficult to remove from the area of Jakarta and its surroundings based on the calculation of groundwater depth.Keywords: inundation, lithology, groundwater level